Il trattamento dei pazienti psichiatrici autori di reato all’interno delle REMS - Morettiu, Germana; Censi, Viviana; Pompili, Pieritalo; Popoli, Emanuela (Il sogno della farfalla, 2022)
The aim of this article is to describe the establishment of new facilities replacing old Italian forensic hospitals, called Residences for the Execution of Security Measures (REMS). It represents a historical progress for the mental health treatment of psychiatric patients that committed crimes. Based on the community residential-home model, REMS represents an interface between territorial mental health services and justice offices. In this article the authors analyze the weaknesses and strengths of this new reform.